IMPLEMENTATION OF ARTIFICIAL INSEMINATION FIXED TIME AND IMPACT ON RURAL PROPERTIES OF FAMILY FARMERS IN THE APL LÁCTEO OESTE GOIANO - Alves Xavier, Vitor; Althair Ribeiro Cordeiro, Fábio; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2023)
Food consumption in the world has been increasing over the years, as has the consumption of meat and milk, with this becoming an increasingly competitive market, demanding higher production quality and its indices, obtaining greater productivity in less time and less animals per space or greater AU per animal. To achieve this, better reproductive rates of herds are needed to achieve greater profitability. Bovine females are considered non-seasonal polyestrous animals and their estrous cycle lasts an average of 21 days, divided into proestrus, estrus, metestrus and diestrus. The present study aims to verify the impact of artificial insemination on rural properties in the municipalities of the APL Lácteo in western Goiás for 12 months, and its relationship with nutrition, it was introduced in 215 rural properties of family farmers and its impact was evaluated according to with a rural dairy farm production system, totaling 2560 animals evaluated, 1914 registered and inseminated.